Calidad de agua y estado situacional de la actividad piscícola en la cuenca media y baja del Río Morona, Distrito de Morona, Provincia Datem del Marañon – Loreto - Sánchez Reategui, Bladimir Tercero (2025)
The present research aimed to describe the situational status of fish farming activity and the water quality of the ponds built in the middle and lower basin of the Morona district during the years 2021–2022. The study population included members of the Kapawi Fish Farmers Association of Morona, settled in Puerto Alegría, as well as beneficiaries from communities in the lower basin linked to the productive model and family management. Two instruments were developed for the methodological approach: one to collect primary and secondary information from the beneficiaries, the ponds, and the communities; and another to record the characteristics of the water resource, including its physicochemical variables and quality standards for sustainable production. Primary data was gathered through structured surveys and direct observation of fish ponds, evaluating fish production and its end use. Secondary data was obtained from official sources, such as the municipalities of Datem del Marañón and Morona. The results show progress in fish farming activity, although some ponds still have low production or are used only for self-consumption. Meanwhile, the water quality of the fish ponds is in good condition. It is concluded that the middle and lower zones of the Morona district have favorable conditions for fish farming development with positive ecological and social impacts, constituting a strategic food resource that strengthens food sovereignty and improves fish farmers’ incomes without harming the natural environment.